2009
DOI: 10.1007/s11693-009-9031-x
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Synthetic Biology: from the lab via the media to the broader public

Abstract: We present insights from a study on communicating Synthetic Biology conducted in 2008. Scientists were invited to write press releases on their work; the resulting texts were passed on to four journalists from major Austrian newspapers and magazines. The journalists in turn wrote articles that were used as stimulus material for eight group discussions with select members of the Austrian public. The results show that, from the lab via the media to the general public, communication is characterized by two import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Newspaper articles about synthetic biology were presented to eight groups of the Austrian lay public. These groups formed focus groups which allowed for quantitative and qualitative analyses (for more details see Kronberger et al, 2009). The newspaper articles were written by four Austrian science and health journalists who were each asked to write one article, sticking to the format and style of the newspapers they usually work for (three daily newspapers and one weekly magazine, covering both high quality and tabloid formats).…”
Section: Methodsmentioning
confidence: 99%
“…Newspaper articles about synthetic biology were presented to eight groups of the Austrian lay public. These groups formed focus groups which allowed for quantitative and qualitative analyses (for more details see Kronberger et al, 2009). The newspaper articles were written by four Austrian science and health journalists who were each asked to write one article, sticking to the format and style of the newspapers they usually work for (three daily newspapers and one weekly magazine, covering both high quality and tabloid formats).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, it is of utmost importance to try to find a-shifting and negotiable-balance of both the persistent need for scientific institutions and gatekeepers, expert knowledge, and space for risky and ambitious scientific endeavors on the one hand, as well as allowing more active participation and reducing extant barriers of power on the other. [107][108][109][110][111] Furthermore, a study conducted with US citizens reveals enthusiasm for synthetic biology applications if they aim at finding solutions for societal, medical, and sustainability needs. [99] At this juncture, the important point about openness is that different interests are handled with transparency and are given equal weight when they concern the same regulatory point.…”
Section: In Science We Trust? Public Perceptions Of Sbmentioning
confidence: 99%
“…[106] Supportive attitudes have mainly been expressed concerning medical applications. [107][108][109][110][111] Furthermore, a study conducted with US citizens reveals enthusiasm for synthetic biology applications if they aim at finding solutions for societal, medical, and sustainability needs. Conversely, emerging biotechnologies are perceived as causes for potential concern if this research is done without investigations into their potential risks and long-term implications.…”
Section: In Science We Trust? Public Perceptions Of Sbmentioning
confidence: 99%
“…Given that biotechnology may represent an important benchmark against which synthetic biology is being evaluated by the public (Kronberger et al, 2009), one might predict similar societal concerns to arise in the agrifood sector. Pauwels (2009) notes that, the participants in their US study reported being unfamiliar with synthetic biology and its applications, their perceptions and related attitudes were framed by those they already held about existing biotechnologies such as GM and cloning (Pauwels, 2013).…”
Section: Consumer Researchmentioning
confidence: 99%